Simulation‐based education for transfusion medicine. Issue 4 (13th November 2014) - Morgan, Shanna; Rioux‐Masse, Benjamin; Oancea, Cristina; Cohn, Claudia; Harmon, James; Konia, Mojca
<x xml:space="preserve">Abstract</x> Background The administration of blood products is frequently determined by physicians without subspecialty training in transfusion medicine (TM). Education in TM is necessary for appropriate utilization of resources and maintaining patient safety. Our institution developed an efficient simulation‐based TM course with the goal of identifying key topics that could be individualized to learners of all levels in various environments while also allowing for practice in an environment where the patient is not placed at risk. Study Design and Methods A 2.5‐hour simulation‐based educational activity was designed and taught to undergraduate medical students rotating through anesthesiology and TM elective rotations and to all Clinical Anesthesia Year 1 (CA‐1) residents. Content and process evaluation of the activity consisted of multiple‐choice tests and course evaluations. Results Seventy medical students and seven CA‐1 residents were enrolled in the course. There was no significant difference on pretest results between medical students and CA‐1 residents. The posttest results for both medical students and CA‐1 residents were significantly higher than pretest results. The results of the posttest between medical students and CA‐1 residents were not significantly different. Conclusion The TM knowledge gap is not a trivial problem as transfusion of blood products is associated with significant risks. Innovative educational techniques are needed to address the ongoing challenges with knowledge acquisition and retention in already full curricula. Our institution developed a feasible and effective way to integrate TM into the curriculum. Educational activities, such as this, might be a way to improve the safety of transfusions.